Inovasi Corporate Social Responsibility: Inisiatif ‘Makin Mesra’ untuk Penanggulangan Kemiskinan di Kabupaten Aceh Barat - Ikhsan; Hajad, Vellayati; Saputra, Ilham Mirza; Maulida, Irham; Setiawan, Deni (Jurnal Bina Praja, 2024)
Innovation of Corporate Social Responsibility (CSR) of Makin Mesra reduces West Aceh District's poverty. CSR of Makin Mesra is a collaborative effort between the local government and private companies to address the region's poverty challenges. The research method used a qualitative approach with case studies to understand the impact and challenges of the program in depth. Data were collected through interviews with key parties, including government officials, company representatives, and community members. The research findings reveal that CSR Makin Mesra has resulted in significant improvements in the welfare of the target community, including a decrease in poverty and unemployment rates. The program has facilitated increased economic activity and essential support for marginalized groups. However, challenges such as limited human resources, delays in fund distribution, and differences in beneficiary data hinder the program's implementation, efficiency, and impact in reducing poverty. This study concludes that CSR Makin Mesra is an essential innovation in utilizing corporate social responsibility for poverty alleviation. This innovation shows positive results in improving community welfare and economic stability. Despite the challenges, the program highlights the potential of collaborative CSR efforts in addressing complex social issues effectively. The author's recommendations to improve the effectiveness of CSR Makin Mesra include strengthening the capacity of the human resources involved through training and skills development of the implementation team and simplifying the fund distribution process through reforming the fund submission and distribution procedures.